The Influence of Project-Based Learning Model on Student Learning Independence in Science And Social Studies Subjects (IPAS) Class IV at UPT SPF SD Inpres Maccini, Makassar City (Tamaddun, 2025)
The problem in this study is the low learning independence of students in the Natural and Social Sciences (IPAS) class IV subject at UPT SPF SD Inpres Maccini, Makassar City. Many students are still dependent on the teacher's direction and are not able to learn independently. This study aims to determine the use and influence of the project-based learning model (PjBL) on student learning independence. This research is a type of quasi experimental research with a nonequivalent control group design. The research population is all students of grade IV of UPT SPF SD Inpres Maccini, Makassar City which totals 71 students. The sampling technique uses purposive sampling to determine a homogeneous class, then continues with random sampling through lots to determine the experimental class and the control class. The research sample consisted of class IV A as an experimental class with 25 students applying the PjBL model, and class IV B as a control class with 23 students using conventional learning. Data collection uses observations and validated learning independence questionnaires. Data analysis used a t-test with a significance level of 5%. The results show that the use of the PjBL model can increase students' learning independence through collaborative learning, with students playing an active role in completing projects and teachers playing the role of facilitators. In addition, there is a significant influence of the PjBL model on student learning independence, as evidenced by a significance value of 0.0058 < 0.05 in the t-test. The average post test score of learning independence in the experimental class was 95.2, which was significantly higher than that of the control class, which was 88.43. Based on these results, it can be concluded that the PjBL model is effective in increasing student learning independence and has a significant positive influence on social studies learning in grade IV UPT SPF SD Inpres Maccini, Makassar City.